Polyamine pathway is associated with muscle anabolic effects by androgen receptor ligand. Issue 1 (19th November 2020) - Kanou, Masanobu; Nakamura, Katsuyuki; Horie, Kyohei; Sakai, Hiroshi; Yanagihara, Yuta; Sakakibara, Iori; Yamana, Kei; Imai, Yuuki
Abstract: Background: Muscle wasting is a common condition concomitant with aging. Androgens significantly increase skeletal muscle mass, but the role of the androgen receptor (AR) in skeletal muscle is not well established. TEI‐SARM2, a novel selective androgen receptor modulator (SARM), was developed as a pharmaceutical candidate for the treatment of muscle wasting diseases. Methods: The efficacy and specificity of TEI‐SARM2 were analysed in vitro assays, and efficacy was also evaluated in vivo using orchiectomized male rats, rat tail‐suspension, rat and mice cancer‐induced muscle atrophy models, and female cynomolgus monkeys. Male myofibre‐specific AR‐knockout (mARKO) mice were orchiectomized to investigate the role of AR in muscle using TEI‐SARM2. RNA‐seq analysis of bulbocavernosus muscle was performed. The effects of spermidine were evaluated in C2C12 myoblasts. Results: Selective, potent anabolic effects of TEI‐SARM2 in muscle were detected in rats and monkeys. TEI‐SARM2 inhibited muscle loss and promoted muscle recovery in a model of muscle disuse and prevented muscle wasting and improved survival rate in cancer models. In vivo and RNA‐seq analyses revealed that AR regulates skeletal muscle mass in myofibres and extra‐myofibres, both directly and indirectly. Among them, polyamine synthesis‐related genes were focused, and spermidine treatment could induce C2C12 cell proliferation. Conclusions: TEI‐SARM2 exhibited potent and selective anabolic effects in muscles, as well as tissue specificity in various animal models. The results support that TEI‐SARM2 is a promising drug candidate for muscle wasting diseases. TEI‐SARM2 induced anabolic effects on skeletal muscle via AR in myofibres as well as other androgen target cells.